Anion-doped cobaltosic oxide as well as preparation method and application thereof

By adopting anion doping technology in tetraoxide and triangular materials, combined with surface flamefluoro and gas covering methods, the problem of the stability and electrochemical performance of the material when the AL doping volume is high. Excellent stability and electrochemical properties under voltage.

CN119370901AActive Publication Date: 2025-01-28JINGMEN GEM NEW MATERIAL CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411497694.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-01-28
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

At higher voltages, cobalt oxide materials with higher Al doping are prone to uneven Al distribution, calcination and cracking, and side reactions with the electrolyte, resulting in serious attenuation of circulation capacity and thermal stability.

Method used

Adopt the method of tetraoxide preparation method doped by the anionic ions, and burn the alternative F -doped cobalt -doped cobalt oxide by mixing the AL mixed cobalt oxide and fluorine sources, and use the gas -phase coverage method Stability and electrochemical performance.

Benefits of technology

It improves the stability and electrochemical performance of lithium cobaltate under high voltage. The first discharge capacity of the 1C rate can reach more than 177mAh/G, and the capacity retention rate after the circulation of 100 circles can reach more than 85%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005101694280000101
    Figure BDA0005101694280000101
  • Figure BDA0005101694280000111
    Figure BDA0005101694280000111
Patent Text Reader

Abstract

The invention discloses anion-doped cobaltosic oxide as well as a preparation method and application thereof. The preparation method comprises the following steps: 1) mixing Al-doped cobalt oxide with a first fluorine source, and calcining to obtain surface F-doped cobalt oxide; and 2) carrying out F coating on the F-doped cobalt oxide on the surface layer by using a second fluorine source and a gas phase coating method to obtain anion-doped cobaltosic oxide. According to the method disclosed by the invention, Al doping is carried out in a bulk phase wet doping manner, and the stability and electrochemical performance of lithium cobalt oxide at high voltage can be improved by combining surface layer pyrogenic process F doping and outer layer gas phase F coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of batteries, and relates to anion-doped cobalt tetroxide and a preparation method and application thereof. Background Art

[0002] In order to cope with the rapidly growing market demand, the voltage of lithium cobalt oxide has been continuously improved, and has increased from 4.3V to 4.5V or even higher. The direction of increasing the voltage of commercial lithium cobalt oxide is generally to dope with Al in the wet synthesis precursor stage. The higher the Al doping amount, the more stable the structure, and the voltage can be greatly improved.

[0003] CN111115710A discloses a method for preparing aluminum-doped cobalt oxide, which comprises the following steps: adding a reaction base liquid into a reactor and heating it, then adding an aluminum-containing cobalt salt solution, a sodium hydroxide solution, and an oxidant into the reaction base liquid in parallel, and controlling the pH value of the reaction system, and then stirring until the reaction is complete to obtain an aluminum-containing cobalt hydroxide slurry, and then aging, filtering, washing, drying, and deironing the aluminum-containing cobalt hydroxide slurry in sequence to obtain an aluminum-containing cobalt hydroxide powder, and calcining the aluminum-containing cobalt hydroxide powder according to a temperature curve to obtain aluminum-doped cobalt oxide. In this way, the present invention improves the cycle performance of cobalt oxide as a battery material while reducing the cost by doping aluminum in cobalt oxide.

[0004] CN118183869A discloses an aluminum-doped cobalt carbonate, an aluminum-doped cobalt oxide, and a preparation method and application thereof. An aluminum-doped cobalt hydroxide shell is formed on an aluminum-doped cobalt carbonate core by an anion-cation exchange method, and then the aluminum-doped cobalt carbonate is sequentially sintered at low temperature and high temperature to obtain aluminum-doped cobalt oxide.

[0005] However, when the Al doping level is high, problems such as uneven Al distribution and calcination cracking will occur. At higher voltages, side reactions will occur with the electrolyte, resulting in serious attenuation of the cycle capacity and thermal stability.

[0006] Therefore, providing a cobalt trioxide and a preparation method thereof so that the lithium cobalt oxide prepared by using the cobalt trioxide has excellent high voltage stability and electrochemical performance is a technical problem that needs to be solved urgently. Summary of the invention

[0007] In view of the above technical problems existing in the prior art, the purpose of the present invention is to provide an anion-doped cobalt tetroxide and a preparation method and application thereof.

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing anion-doped cobalt tetroxide, characterized in that the preparation method comprises the following steps:

[0010] (1) mixing Al-doped cobalt oxide with a first fluorine source and calcining to obtain surface F-doped cobalt oxide;

[0011] (2) Using a second fluorine source, the surface fluorine-doped cobalt oxide is coated with fluorine by a gas phase coating method to obtain anion-doped cobalt tetroxide.

[0012] The method of the present invention uses Al-doped cobalt oxide, which can greatly improve the voltage platform of the material; by first performing pyrometallurgical doping with F, on the one hand, F doping of the surface layer of cobalt oxide is achieved, achieving the synergistic effect of Al and F co-doping, and on the other hand, a part of F will form a point-like coating on the surface of the material, and by using the gas phase coating method to carry out F coating, it can be connected with the point-like coating to form a continuous film. The above factors work together to protect the material from corrosion by the electrolyte at high voltage, and improve the stability and electrochemical performance of the material. The lithium cobalt oxide prepared by the anion-doped cobalt oxide prepared by the present invention has excellent high voltage stability and electrochemical performance.

[0013] At the same time, using the pyrolysis method to dope F on the surface of cobalt oxide can perfectly solve the problem of difficult wastewater treatment caused by F doping in the wet co-precipitation stage, as well as the problem of inaccurate F doping amount in the positive electrode calcination stage.

[0014] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0015] Preferably, the method for preparing the Al-doped cobalt oxide comprises the following steps:

[0016] (a) adding a cobalt-aluminum mixed solution and a precipitant solution to a base solution to perform a coprecipitation reaction to obtain a F-doped precursor;

[0017] (b) sintering the F-doped precursor to obtain Al-doped cobalt oxide.

[0018] The method of the present invention utilizes a bulk wet doping method to perform Al doping, combined with surface pyrolysis F doping and outer gas phase F coating, to improve the stability and electrochemical performance of lithium cobalt oxide at high voltage.

[0019] Preferably, the concentration of Co element in the cobalt-aluminum mixed solution in step (a) is 90-130 g / L, for example, it can be 90 g / L, 95 g / L, 100 g / L, 105 g / L, 110 g / L, 115 g / L, 120 g / L, 125 g / L or 130 g / L, etc.

[0020] Preferably, the Co element in the cobalt-aluminum mixed solution in step (a) is derived from CoCl 2 、CoSO 4 、Co(NO 3 ) 2 At least one of .

[0021] Preferably, the concentration of Al element in the cobalt-aluminum mixed solution in step (a) is 0.1-2.5 g / L, for example, 0.1 g / L, 0.15 g / L, 0.2 g / L, 0.3 g / L, 0.4 g / L, 0.45 g / L, 0.5 g / L, 0.6 g / L, 0.8 g / L, 1 g / L, 1.2 g / L, 1.3 g / L, 1.5 g / L, 1.7 g / L, 1.8 g / L, 2 g / L, 2.2 g / L, 2.3 g / L, 2.4 g / L or 2.5 g / L, etc.

[0022] Preferably, the Al element in the cobalt-aluminum mixed solution of step (a) is derived from at least one of aluminum chloride, aluminum nitrate, aluminum sulfate and aluminum acetate.

[0023] Preferably, the precipitant in the precipitant solution of step (a) comprises Na 2 CO 3 NH 4 HCO 3 and NaHCO 3 At least one of .

[0024] Preferably, the concentration of the precipitant solution in step (a) is 200-260 g / L, for example, it can be 200 g / L, 210 g / L, 220 g / L, 230 g / L, 240 g / L, 250 g / L or 260 g / L.

[0025] Preferably, the base liquid in step (a) is water or a precipitant solution, and the concentration of the base liquid is 0-50 g / L, for example, 0, 0.1 g / L, 0.3 g / L, 0.5 g / L, 1 g / L, 3 g / L, 5 g / L, 7 g / L, 10 g / L, 12 g / L, 14 g / L, 15 g / L, 20 g / L, 25 g / L, 30 g / L, 35 g / L, 40 g / L, 45 g / L or 50 g / L, etc. Wherein, when the concentration of the base liquid is 0, the base liquid is water; when the concentration of the base liquid is not 0, the base liquid is a precipitant solution.

[0026] Preferably, the pH of the coprecipitation reaction in step (a) is 7.0-7.6, for example, it can be 7.0, 7.1, 7.2, 7.3, 7.4, 7.5 or 7.6.

[0027] Preferably, the temperature of the coprecipitation reaction in step (a) is 40-60°C, for example, it can be 40°C, 42°C, 44°C, 45°C, 46°C, 48°C, 50°C, 52°C, 53°C, 55°C, 56°C, 58°C or 60°C, etc.

[0028] In one embodiment, after the coprecipitation reaction in step (a) reaches the stopping particle size, washing and drying are performed.

[0029] Preferably, the sintering temperature in step (b) is 500-800°C, for example, it can be 500°C, 525°C, 550°C, 570°C, 580°C, 600°C, 625°C, 650°C, 660°C, 680°C, 700°C, 725°C, 750°C, 770°C, 780°C or 800°C, etc.

[0030] As a preferred technical solution of the preparation method of the present invention, the first fluorine source in step (1) is ammonium fluoride. The present invention uses a volatile fluorine source for pyrometallurgical fluorine doping, which is conducive to achieving uniform doping on the surface of the material.

[0031] Preferably, the mass ratio of the Al-doped cobalt oxide to the first fluorine source in step (1) is 150-1100, for example, it can be 150, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1050 or 1100, etc.

[0032] Preferably, the calcination temperature in step (1) is 250-450°C, for example, it can be 250°C, 260°C, 280°C, 300°C, 315°C, 330°C, 340°C, 350°C, 360°C, 380°C, 400°C, 410°C, 415°C, 430°C, 440°C or 450°C, etc.

[0033] The method of the present invention performs pyrometallurgical F-doping at a relatively low temperature, and can dope F on the surface layer of the material to improve the performance of the material.

[0034] Preferably, the calcination holding time in step (1) is 2-6 h, for example, 2 h, 2.5 h, 3 h, 4 h, 5 h or 6 h.

[0035] As a preferred technical solution of the preparation method of the present invention, the second fluorine source in step (2) is sodium fluorosilicate.

[0036] Preferably, in step (2), based on 3000g of surface F-doped cobalt oxide, the amount of the second fluorine source used is 2.4-15g, for example, 2.5g, 3g, 3.5g, 4g, 5g, 5.5g, 6g, 7g, 8g, 9g, 10g, 11g, 12g, 13g, 14g or 15g, etc.

[0037] Preferably, the heating temperature for the gas phase coating in step (2) is 350-450°C, for example, it can be 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, 410°C, 420°C, 430°C, 440°C or 450°C, etc.

[0038] Preferably, the method for gas phase coating in step (2) is: setting an isolation piece in a closed container to divide the closed container into an upper part and a lower part, placing the surface F-doped cobalt oxide on the upper part of the isolation piece, placing a second fluorine source below the isolation piece, heating the second fluorine source to generate fluorine-containing vapor, and coating the surface F-doped cobalt oxide.

[0039] In one embodiment, the separator is a metal mesh, and the material of the metal should not participate in the chemical reaction.

[0040] In a second aspect, the present invention provides an anion-doped cobalt tetroxide, wherein the anion-doped cobalt tetroxide is prepared by the method described in the first aspect.

[0041] In a third aspect, the present invention provides a positive electrode, wherein the positive electrode comprises the anion-doped cobalt tetroxide described in the second aspect.

[0042] In a fourth aspect, the present invention provides a battery, comprising the positive electrode described in the third aspect.

[0043] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] (1) The method of the present invention uses Al-doped cobalt oxide, which can greatly improve the voltage platform of the material; by first performing pyrometallurgical F doping, on the one hand, F doping of the surface layer of cobalt oxide is achieved, achieving the synergistic effect of Al and F co-doping; on the other hand, a portion of F will form a point-like coating on the surface of the material. By using the gas phase coating method to perform F coating, it can be connected with the point-like coating to form a continuous film. The above factors work together to protect the material from corrosion by the electrolyte at high voltage, thereby improving the stability and electrochemical performance of the material.

[0046] (2) The lithium cobalt oxide prepared by using the anion-doped cobalt oxide prepared by the present invention has excellent high voltage stability and electrochemical performance. The first discharge capacity at 1C rate can reach more than 177 mAh / g, and the capacity retention rate after 100 cycles can reach more than 85%. DETAILED DESCRIPTION

[0047] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0048] Example 1

[0049] This embodiment provides a method for preparing anion-doped cobalt tetroxide, comprising the following steps:

[0050] Step 1: Prepare cobalt-aluminum mixed solution A (the concentration of Co element is 130 g / L, and Co element comes from CoCl 2 , the concentration of Al element is 1.5g / L, Al element comes from aluminum acetate), precipitant solution B (NH 4 HCO 3 Solution, concentration is 260g / L);

[0051] Step 2: Add 50 g / L NH 4 HCO 3 The solution is used as the base solution, and the cobalt-aluminum mixed solution A and the precipitant solution B are simultaneously pumped into the reactor for co-precipitation reaction. During the co-precipitation reaction, the pH of the reaction system is controlled to be 7.6 and the temperature is 60°C.

[0052] Step 3: After the reaction reaches the stopping particle size, the particles are washed and dried, and calcined at 800° C. to obtain cobalt oxide.

[0053] Step 4: The cobalt oxide obtained in step 3 is mixed with ammonium fluoride in a mass ratio of 500, and the mixture is heated at 450° C. for 6 hours to obtain surface F-doped cobalt tetroxide.

[0054] Step 5: Use a sealed container with a horizontally arranged separator, place 3000 g of surface F-doped cobalt tetroxide on the separator, place 7.5 g of sodium fluorosilicate under the separator, heat the sodium fluorosilicate to 450°C to generate fluorine-containing steam, and coat the surface F-doped cobalt tetroxide to obtain anion-doped cobalt tetroxide.

[0055] Example 2

[0056] This embodiment provides a method for preparing anion-doped cobalt tetroxide, comprising the following steps:

[0057] Step 1: Prepare cobalt-aluminum mixed solution A (the concentration of Co element is 100 g / L, and Co element comes from CoCl 2 , the concentration of Al element is 1.0 g / L, Al element comes from aluminum acetate), precipitant solution B (NH 4 HCO 3 solution, concentration is 200g / L);

[0058] Step 2: Add 50 g / L NH 4 HCO 3 The solution is used as the base solution, and the cobalt-aluminum mixed solution A and the precipitant solution B are simultaneously pumped into the reactor for co-precipitation reaction. During the co-precipitation reaction, the pH of the reaction system is controlled to be 7.3 and the temperature is 45°C.

[0059] Step 3: After the reaction reaches the stopping particle size, the particles are washed and dried, and calcined at 550° C. to obtain cobalt oxide.

[0060] Step 4: The cobalt oxide obtained in step 3 is mixed with ammonium fluoride in a mass ratio of 1000, and the mixture is heated at 250° C. for 6 hours to obtain surface F-doped cobalt tetroxide.

[0061] Step 5: Use a sealed container with a horizontally arranged separator, place 3000 g of surface F-doped cobalt tetroxide on the separator, place 2.5 g of sodium fluorosilicate under the separator, heat the sodium fluorosilicate to 400°C to generate fluorine-containing steam, and coat the surface F-doped cobalt tetroxide to obtain anion-doped cobalt tetroxide.

[0062] Example 3

[0063] This embodiment provides a method for preparing anion-doped cobalt tetroxide, comprising the following steps:

[0064] Step 1: Prepare cobalt-aluminum mixed solution A (the concentration of Co element is 115 g / L, and Co element comes from CoSO 4 , the concentration of Al element is 1.2g / L, Al element comes from aluminum acetate), precipitant solution B (Na 2 CO 3 Solution, concentration is 230g / L);

[0065] Step 2: Add 30g / L of Na 2 CO 3 The solution is used as the base solution, and the cobalt-aluminum mixed solution A and the precipitant solution B are simultaneously pumped into the reactor for co-precipitation reaction. During the co-precipitation reaction, the pH of the reaction system is controlled to be 7.5 and the temperature is 50°C.

[0066] Step 3: After the reaction reaches the stopping particle size, the particles are washed and dried, and calcined at 650° C. to obtain cobalt oxide.

[0067] Step 4: The cobalt oxide obtained in step 3 is mixed with ammonium fluoride in a mass ratio of 200, and the mixture is heated at 350° C. for 4 hours to obtain surface F-doped cobalt tetroxide.

[0068] Step 5: Use a sealed container with a horizontally arranged separator, place 3000 g of surface F-doped cobalt tetroxide on the separator, place 15 g of sodium fluorosilicate under the separator, heat the sodium fluorosilicate to 380°C to generate fluorine-containing steam, and coat the surface F-doped cobalt tetroxide to obtain anion-doped cobalt tetroxide.

[0069] Example 4

[0070] This embodiment provides a method for preparing anion-doped cobalt tetroxide, comprising the following steps:

[0071] Step 1: Prepare a cobalt-aluminum mixed solution A (the concentration of the Co element is 90 g / L, and the Co element comes from Co(NO 3 ) 2 , the concentration of Al element is 0.5 g / L, Al element comes from aluminum nitrate), precipitant solution B (NaHCO 3 Solution, concentration is 240g / L);

[0072] Step 2: Add water into the reactor as the base liquid, and pump the cobalt-aluminum mixed solution A and the precipitant solution B into the reactor at the same time for co-precipitation reaction. During the co-precipitation reaction, the pH of the reaction system is controlled to be 7.0 and the temperature is controlled to be 40°C.

[0073] Step 3: After the reaction reaches the stopping particle size, the particles are washed and dried, and calcined at 700° C. to obtain cobalt oxide.

[0074] Step 4: The cobalt oxide obtained in step 3 is mixed with ammonium fluoride in a mass ratio of 650, and the mixture is kept at 300° C. for 5 hours to obtain surface F-doped cobalt tetroxide.

[0075] Step 5: Use a sealed container with a horizontally arranged separator, place 3000 g of surface F-doped cobalt tetroxide on the separator, place 10 g of sodium fluorosilicate under the separator, heat the sodium fluorosilicate to 360°C to generate fluorine-containing steam, and coat the surface F-doped cobalt tetroxide to obtain anion-doped cobalt tetroxide.

[0076] Example 5

[0077] The difference between this embodiment and embodiment 1 is that the amount of sodium fluorosilicate used is 2.3 g.

[0078] Example 6

[0079] The difference between this embodiment and embodiment 1 is that the amount of sodium fluorosilicate used is 15.1 g.

[0080] Comparative Example 1

[0081] This comparative example provides a cobalt tetroxide material, which is different from Example 1 in that step 4 is not performed.

[0082] Comparative Example 2

[0083] This comparative example provides a cobalt trioxide material, which is different from Example 1 in that step five is not performed.

[0084] Comparative Example 3

[0085] This comparative example provides a cobalt tetroxide material, which is different from Example 1 in that the cobalt-aluminum mixed solution A in step 1 is replaced by CoCl 2 The concentration of Co in the solution is the same as that in Example 1.

[0086] Preparation of lithium cobalt oxide positive electrode material:

[0087] The anion-doped cobalt tetroxide prepared in Example 1-6 and the cobalt tetroxide prepared in Comparative Example 1-3 were used as precursor materials. The precursor materials and lithium carbonate were weighed separately at a lithium-cobalt molar ratio (Li / Co) of 1.025. After mixing them, they were sintered in a box furnace at 1100°C in an air atmosphere for 9 hours. After sintering, the product was crushed, deironed, and sieved to obtain a lithium cobalt oxide positive electrode material.

[0088] Performance test of lithium cobalt oxide positive electrode material:

[0089] Preparation of lithium-ion batteries:

[0090] The lithium cobalt oxide positive electrode material prepared by the above method is used as the positive electrode active material, 80wt% of the positive electrode active material, 10wt% of Super-P and 10wt% of polyvinylidene fluoride (PVDF) are dispersed in N-methylpyrrolidone (NMP) solution to prepare an electrode slurry, which is coated on an aluminum foil and dried to obtain a positive electrode;

[0091] The lithium sheet is the negative electrode;

[0092] The separator is a Φ19 PP microporous membrane (Celgard2400);

[0093] The composition of the electrolyte is: 1M LiPF 6 A mixture with EC, DMC and EMC (EC:DMC:EMC volume ratio = 1:1:1).

[0094] The positive electrode, separator, negative electrode and electrolyte are assembled to obtain a button battery.

[0095] The performance of the lithium ion battery assembled by preparing the lithium cobalt oxide positive electrode material with the cobalt oxide provided in Examples 1-6 and Comparative Examples 1-3 was tested under the following test conditions: the cycle test was performed at 1C in the electrochemical window of 3.0-4.6V to obtain the first discharge capacity and the capacity retention rate after 100 cycles. The test results are shown in Table 1.

[0096] Table 1

[0097]

[0098]

[0099] As can be seen from Table 1, the method of the present invention utilizes bulk wet doping to perform Al doping, combined with surface pyrolysis F doping and outer gas phase F coating, to improve the stability and electrochemical performance of lithium cobalt oxide at high voltage.

[0100] At the same time, through the comparison between Example 1 and Examples 5-6, it can be seen that when the F doping coating amount is within a certain range, better electrical performance can be obtained.

[0101] By comparing Example 1 with Comparative Example 1, it can be seen that when fluorine is not doped externally but only chemically deposited, both the initial capacity and the cycle performance will decrease.

[0102] By comparing Example 1 with Comparative Example 2, it can be seen that when only fluorine doping is performed externally without chemical deposition, the initial capacity decreases and the cycle performance decreases significantly.

[0103] By comparing Example 1 with Comparative Example 3, it can be seen that Al doping affects the capacity of the material, and synergistically affects the initial capacity and cycle performance with F.

[0104] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing anion-doped cobalt tetroxide, characterized in that: The preparation method comprises the following steps: (1) mixing Al-doped cobalt oxide with a first fluorine source and calcining to obtain surface F-doped cobalt oxide; (2) Using a second fluorine source, the surface fluorine-doped cobalt oxide is coated with fluorine by a gas phase coating method to obtain anion-doped cobalt tetroxide.

2. The preparation method according to claim 1, characterized in that: The preparation method of the Al-doped cobalt oxide comprises the following steps: (a) adding a cobalt-aluminum mixed solution and a precipitant solution to a base solution to perform a coprecipitation reaction to obtain a F-doped precursor; (b) sintering the F-doped precursor to obtain Al-doped cobalt oxide.

3. The preparation method according to claim 2, characterized in that: The concentration of the Co element in the cobalt-aluminum mixed solution of step (a) is 90-130 g / L; Preferably, the Co element in the cobalt-aluminum mixed solution of step (a) is derived from at least one of CoCl2, CoSO4, and Co(NO3)2; Preferably, the concentration of Al element in the cobalt-aluminum mixed solution in step (a) is 0.1-2.5 g / L; Preferably, the Al element in the cobalt-aluminum mixed solution of step (a) is derived from at least one of aluminum chloride, aluminum nitrate, aluminum sulfate and aluminum acetate.

4. The preparation method according to claim 2 or 3, characterized in that: The precipitant in the precipitant solution of step (a) comprises at least one of Na2CO3, NH4HCO3 and NaHCO3; Preferably, the concentration of the precipitant solution in step (a) is 200-260 g / L; Preferably, the base liquid in step (a) is water or a precipitant solution, and the concentration of the base liquid is 0-50 g / L; Preferably, the pH of the coprecipitation reaction in step (a) is 7.0-7.6; Preferably, the temperature of the coprecipitation reaction in step (a) is 40-60°C; Preferably, the sintering temperature in step (b) is 500-800°C.

5. The preparation method according to any one of claims 1 to 4, characterized in that: Step (1) the first fluorine source is ammonium fluoride; Preferably, in step (1), the mass ratio of the Al-doped cobalt oxide to the first fluorine source is 150-1100; Preferably, the calcination temperature in step (1) is 250-450°C; Preferably, the calcination holding time in step (1) is 2-6 hours.

6. The preparation method according to any one of claims 1 to 5, characterized in that: Step (2) the second fluorine source is sodium fluorosilicate; Preferably, in step (2), based on 3000 g of surface F-doped cobalt oxide, the amount of the second fluorine source is 2.4-15 g; Preferably, the heating temperature of the gas phase coating in step (2) is 350-450°C.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The gas phase coating method in step (2) is: An isolation piece is set in a sealed container to divide the sealed container into an upper part and a lower part, and the surface F-doped cobalt oxide is placed on the isolation piece, and a second fluorine source is placed below the isolation piece. The second fluorine source is heated to generate fluorine-containing vapor to coat the surface F-doped cobalt oxide.

8. Anion-doped cobalt tetroxide, characterized in that: The anion-doped cobalt tetroxide is prepared by the method according to any one of claims 1 to 7.

9. A positive electrode, characterized in that: The positive electrode comprises the anion-doped cobalt tetroxide as claimed in claim 8.

10. A battery, characterized in that: The battery comprises the positive electrode according to claim 9.

Citation Information

Patent Citations

  • Preparation method of aluminum-doped cobalt oxide

    CN111115710A

  • Aluminum-doped cobalt carbonate, aluminum-doped cobaltosic oxide and preparation method and application thereof

    CN118183869A

  • High-voltage and high-cycle type lithium cobalt oxide positive electrode material and preparation method therefor

    CN107591526A

  • Fluorine-doped spinel structure cobaltosic oxide electro-catalytic material and preparation method thereof

    CN111346652A

  • Aluminum-fluorine co-doped cobaltosic oxide as well as preparation method and application thereof

    CN115571924A